Marketing strategy and uncertainty - Jagpal, Sharan (Oxford University Press, 1999)
Marketing Strategy and Uncertainty is unique in content, form, and depth of coverage. It has been successfully class-tested in MBA and Executive Education programs at Columbia University, Rutgers University, and the International University of Japan and is ideal for courses in marketing management, strategy, sales force management, and advertising. The book's integrative approach to strategic decision making will appeal primarily to readers in marketing, but also in economics, finance, organization management, and industrial organization. Because of its unique presentation style, Marketing Strategy and Uncertainty is a must-read for students, executives, and researchers